ISLAM NUSANTARA: AN APPROACH TO PRACTICE ISLAM - Qomar, Mujamil (IAIN Tulungagung, 2019)
Islam Nusantara is not a new religion, a rival of Islam, sect, or a usual mazhab, but actually is a character of thoughtful mazhab or manhaj Islam. Islam Nusantara is just an approach in practicing Islamic teachings, namely cultural approaches. This Islam has the most prominent character which is called as wasathiyah (moderation) that is reflected in some attitude such as, inclusive, tolerant, friendly, respect other parties, friendly with diverse cultures and religions, tasamuh, tawazun, and i’tidal. Islam Nusantara sees local cultures as “oxygen”; filters and then respect good culture and tradition (al-‘urfal-shalih) so it can have a dialogue with the environment around it positively. This cultural approach has been successfully used by the Walisongo in preaching using tembang, Wayang Kulit, socializing key terms, and so on. In the faith, Islam Nusantara is manifested in some rituals, tahlilan, istighasah, haul akbar, and selametan. Furthermore, in fiqh it’s such as imsak, zakat, halal-bihalal, marriage registration, marriage book, and the reading of ta’liq talaq. Islam Nusantara successfully consolidate Islam with nationalism so both of them are harmonious, and bring the tradition together with modernization through slogan al-muhafadzah ‘ala al-qadîm al-salih wa al-akhdz bi al-jadîdal-aslah [keep the old good tradition and take a new and better tradition].